FAKTOR-FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK PERUSAHAAN (Studi Kasus Perusahaan Manufaktur yang Terdaftar di BEI tahun 2011-2014) - Dewan Akbar Shidarta, 12.05.52.0145; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2017)
This study aims to analyze the influence of liquidity, leverage, independent commissioner, and earnings management against aggressive action taxes manufacturing companies period 2011-2014 listed on the Indonesia Stock Exchange.Â In this study the researchers used the financial data of manufacturing companies listed on the BEI in the period 2011-2014. The method used is purposive sampling method. The test equipment in this study used multiple linear regression, partial test (t test) and simultaneous test f (f test). The result of this research is liquidity and earnings management have negative effect to agriculture aggressiveness of manufacturing company period 2011-2014 which listed in Indonesia Stock Exchange. While leverage and independent commissioner does not affect the aggressiveness of the companys manufacturing tax for the period 2011-2014 listed on the Indonesia Stock Exchange.Keywords: Liquidity, Leverage, Independent Commissioner, Earnings Management, Tax Aggressiveness